Decarbonization pathways for the power sector in Sumatra, Indonesia. (October 2021) - Sani, L.; Khatiwada, D.; Harahap, F.; Silveira, S.
Abstract: The Indonesian power sector faces the combined challenge to (i) satisfy growing electricity demand at an affordable cost and (ii) comply with the decarbonization targets committed under the Paris Agreement. In this study, we investigate cost-optimal pathways for the development of the power sector in line with climate targets. We used the Low Emissions Analysis Platform (LEAP) software tool to build a power-system expansion model for Sumatra and simulated four scenarios representing a business as usual development, the current development plans, and two mitigation pathways in line with the national climate targets. Particular focus is put on bioenergy, an energy source that has been often overlooked in previous studies and plans. The results show that, although the national plans consider mitigation actions, they do not reduce coal dependency. Besides, current development plans are not cost-effective and have high marginal abatement costs for emissions reduction. The two mitigation scenarios achieve better environmental results at lower system costs. Our results show that bioenergy deployment can contribute significantly to achieving the greenhouse gas (GHG) targets of 19% and 24% pledged by the Indonesian government. More efficient use of modern renewables and natural gas can reduce Sumatra's dependence on coal resources. Highlights: High risks for lock-in effects with planned new coal and lignite power plants in Sumatra. Biomass, solar, and wind can significantly reduce the emissions mitigation cost. Higher emissions reductions can be achieved at lower costs than suggested in current plans. Biomass residues provide a cost-competitive alternative for reduction of GHG emissions in the electricity grid. More ambitious climate targets require both shift from coal to natural gas and deployment of renewables.